KONDISI PSIKOSOSIAL ANAK KORBAN TINDAK KEKERASAN SEKSUAL (STUDI KASUS) DI DINAS SOSIAL KABUPATEN CIREBON - Tammah Wiradewi Yudha Yanti; Endah Winarni; pribowo pribowo (Politeknik Kesejahteraan Sosial (Poltekesos) Bandung, 2023)
Psychosocial condition is a condition of a person who is influenced and affects the conditions of physical development, psychological conditions, and social conditions. This study aims to determine: 1) Characteristics of Informants, 2) Physical Conditions of Children Victims of Sexual Violence, 3) Psychological Conditions of Children Victims of Sexual Violence, and 4) Social Conditions of Children Victims of Sexual Violence. The informants in this study were three people with two supporting informants, namely one parent of a child who was a victim of sexual violence and one social rehabilitation assistant at the Cirebon District Social Service. This study uses a descriptive qualitative research method with a case study approach. Three informants were determined by purposive sampling. The data collection techniques used were interviews, participatory observation, and documentation studies. Check the validity of the data using credibility (validity interval), transferability (external validity), dependability (reliability), and confirmability (objectivity). The data analysis technique was carried out by data reduction, data presentation, and conclusion drawing/verification. The results showed that the physical aspects of the informants experienced such as dizziness, weakness, fever, stomach ulcers and not feeling well, sleep disturbances and eating disorders. In the psychological aspect, the informant felt feelings of sadness, anger, loss of self-confidence, hurt and revenge against the perpetrator and wanted a feeling of revenge for his hurt. In the social aspect, the informant does not experience problems and conflicts with anyone, both in the family environment, friendship environment, and living environment. However, the most psychological symptoms felt by the informants, it shows that the informants experience post-traumatic stress. Post-traumatic stress experienced by the informants has not fully recovered